DECISION SUPPORT SYSTEM FOR DETERMINATION OF SCHOLARSHIP USING SCRATCH PROGRAMMING BASED ON SAW METHOD - Gunawan, Indra; Purnomo, Dentaruni Cahya (LPPM STMIK Dharmapala Riau, 2021)
Scholarships are one of the efforts to provide financial assistance or support to individuals who are expected to be able to support the need in the process of taking education. In 2020, 1st State Vocational School of Cepu had more than 1000 students and from 300 scholarship submissions only 9 people managed to get a scholarship. Therefore a tool is needed to select students who are entitled and less entitled to get scholarships. Decision Support System is one of the tools that can be used to calculate to select the students. The method used is Simple Additive Weighting(SAW) because the method is a simple but it’s still an accurate method, because it has a very low error level. The aim of this study is to apply the Simple Additive Weighting(SAW) method for Decision Support System scholarships using Scratch Programming which is a programming language that is fairly newly developed and easy to apply to various attractive creations with a shorter time compared to using other programming languages. The criteria used in this study are parent’s income, parent’s dependents, Home-to-school Distance , and the students age. The results obtained and analyzed from this study concluded that the testing system using Mean Square Error(MSE) has a very low level of error which is equal to 1.3312E-31 it can be said that the system is accurate, and from the test functionality using the Black Box obtained 100% results.